Television Market Size and Political Accountability in the US House of Representatives - Patrick Balles; Ulrich Matter; Alois Stutzer (Institute of Labor Economics (IZA), 2022)
This paper examines the role of local TV market structure in US congressional politics, exploiting variation in the overlaps of political markets and TV markets. Local TV stations are hypothesized to report relatively more per US House representative in less populous markets (where the number of House districts covered is smaller), leading to better informed voters and more accountable representatives. We find that smaller markets are indeed associated with (i) higher coverage of representatives, and (ii) a higher level of voters' knowledge about their representatives. However, (iii) representatives of smaller and more congruent markets are only more likely to decide aligned with their constituents' policy preferences in highly competitive districts. This evidence suggests that local political news coverage on TV serves as a complement rather than a substitute in holding members of the US Congress accountable.
Keywords: D72; L82; 330; political accountability; market congruence; media coverage; TV markets; legislative voting; US Congress; voter knowledge; campaign finance